A Real-time Optoelectronic Device in Screening of Precancerous Cervical Lesion - Rizky Rahmadhany; Junita Indarti (Indonesian Journal of Obstetrics and Gynecology, 2015)
Objective: To obtain the diagnostic values of optoelectronic device for screening of precancerous cervical lesions. Method: We performed a diagnostic study with cross sectional design. Subjects were recruited from Dr. Cipto Mangunkusumo Hospital, from February until December 2013. Subjects were enrolled based on consecutive sampling until the minimum sample was achieved (60 samples). Result: During the study period, 60 patients were enrolled. Sensitivity, specificity, positive predictive value, and negative predictive value of the optoelectronic device were 76%, 95%, 96%, and 64%, respectively. We also investigated diagnostic values of other screening methods, namely citology and colposcopy. Sensitivity and specificity of liquid based cytology were 83% and 63% respectively. The combination of optoelectronic device and liquid based cytology increased the sensitivity to 92.8%. Meanwhile, sensitivity and specificity of colposcopy were 88% and 58%, respectively. Based on Altman criteria, kappa value for optoelectronic device with cytology was 0.35 (fair) and optoelectronic device with colposcopy was 0.45 (moderate). Conclusion: A real-time optoelectronic device might be used as an alternative method in early detection of precancerous cervical lesions, either as a single method or combined with liquid based cytology. Keywords: diagnostic values, optoelectronic device, precancerous cervical lesions